Topical Nepafenac 0.1% or 0.3% for the Treatment of Central Serous Chorioretinopathy: A Case Series of Chronic and Recurrent Disease and Review of the Literature - T. Shaw3, Lincoln; Hariprasad, Ishani; V. Messner, Leonard; A. Bansal, Chandani; A. Schechet, Sidney; Pérez, Janette (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2022)
Central serous chorioretinopathy (CSCR) is a disease involving leakage of serous fluid through the retinal pigment epithelium, resulting in neurosensory retinal detachment. The majority of acute CSCR cases resolve spontaneously. However, treatment options for chronic and recurrent cases are lacking. In this case series, topical nepafenac 0.1% and 0.3% were investigated as novel treatments for chronic and recurrent CSCR. We performed a retrospective case series analysis of six patients diagnosed with chronic recurrent CSCR. Data from patient medical records were collected, including age range, gender, subjective complaints, Snellen visual acuity (VA), clinical eye examination, central macular thickness (CMT) on optical coherence tomography, prior treatments, time of follow-up, and time to resolution of CSCR. The six cases of chronic and recurrent CSCR in this study were treated with 0.1% and/or 0.3% topical nepafenac. The mean age of the six cases was 52 years. There was an average gain in vision of 2.5 lines in Snellen VA, and a final Snellen VA of 20/20 was achieved in each case. The average time to complete resolution of CSCR was 3.33 months. The decrease in CMT ranged from 105 µm to 507 µm, with an average decrease of 240 µm, and subretinal fluid resolved completely in all the six cases.